What If You Can't Ask Them? Psychometric Properties of a Behavioral Assessment of Sibling Relationship Quality. Issue 3 (May 2023) - Agnew, Charlene N.; Fiani, Theresa; Jones, Emily A.
Building on studies of preferences for social interaction in children with autism spectrum disorder (ASD) we sought to provide a way for siblings with ASD to express their perspective about the quality of their sibling relationships. We developed a behavioral assessment of sibling relationship preference (Sibling Relationship Assessment [SRA]) and examined the psychometric properties of test-retest reliability, inter-rater reliability, and convergent validity. The SRA was feasible to administer and revealed expected differences between sibling dyads with one sibling with ASD compared to typically-developing sibling dyads. We found strong positive correlations for inter-rater reliability and test-retest reliability and convergent validity. The SRA provides a way to assess the perspective of the sibling with ASD that taps one characteristic, preference for spending time with one's sibling, of the quality of sibling relationships.